Peripheral vascular trauma in children: related factors by the logistic regression method - Raquel Nogueira Avelar Silva; Cristina Arreguy-Sena (Universidade Federal de Goias, 2014)
The objective of the present study was to identify the factors related to "peripheral vascular trauma" in children aged six months to 12 years. This prospective cohort study included children with peripheral vein punctured for the first time per side and excluded those with high/complete healing of trauma signs after removing the catheter. Daily clinical evaluations were performed in intervals shorter than 24 hours. Data were treated according to Pearson's test and the logistic regression method. Among the 14 variables considered intervenient, four were statistically associated to the occurrence of trauma: dirtiness and humidity in the catheter insertion site, catheter caliber, and age. A causal relationship was found between the intervenient variables and the outcome, "peripheral vascular trauma", thus, contributing to forming the knowledge of the peripheral venous puncture in children aged six months to 12 years. Descriptors: Child; Nursing Diagnosis; Veins; Injuries.